2016
DOI: 10.1016/j.icheatmasstransfer.2016.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation and model development for effective viscosity of MgO–ethylene glycol nanofluids by using dimensional analysis, FCM-ANFIS and GA-PNN techniques

Abstract: Desirable effective viscosity behaviour is an essential transport property required for the effective utilisation of nanofluids in industrial systems as well as other applications. Viscosity influences significantly the pumping power and heat transfer effectiveness in a thermal system since Reynolds and Prandtl numbers are functions of viscosity. In this study, the optimum energy required for the preparation of MgO-ethylene glycol (MgO-EG) nanofluids was determined by varying the ultrasonication energy input i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(29 citation statements)
references
References 46 publications
(62 reference statements)
3
26
0
Order By: Relevance
“…It can be observed that the nanofluid viscosity increases with the volume concentration. Previous studies [27][28][29][30][31][32][33] reported similar results for the viscosities and thermal conductivities of nanofluids. The density and specific heat of the nanofluid were calculated using the following mixing theory equations:…”
Section: Thermophysical Properties Of Nanofluidssupporting
confidence: 72%
See 1 more Smart Citation
“…It can be observed that the nanofluid viscosity increases with the volume concentration. Previous studies [27][28][29][30][31][32][33] reported similar results for the viscosities and thermal conductivities of nanofluids. The density and specific heat of the nanofluid were calculated using the following mixing theory equations:…”
Section: Thermophysical Properties Of Nanofluidssupporting
confidence: 72%
“…Because of the increasing demand for improvements in a heat exchanger's performance, new heat transfer transport fluids called nanofluids were introduced towards the end of the last century. The term 'nanofluid' was first introduced by Choi in 1995 [1], after which many researchers investigated (i) the preparation and thermophysical properties of nanofluids [2][3][4][5][6][7], (ii) forced convection using nanofluids in heat exchangers [8][9][10][11][12][13][14], and (iii) the natural convection of nanofluids in cavities [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The estimated standard uncertainty u r ðgÞ ¼5% and uðTÞ ¼ 0:10K Adio et al [39] proposed another model introduced specially for MgO-EG nanofluids on the basis of nonlinear regression modeling: Figure 4 presents results of ten subsequent measurements of thermal conductivity, and the average calculated based on them. These results show that MgO-EG nanofluids were stable several hours after preparation.…”
Section: Resultsmentioning
confidence: 99%
“…These properties make MgO-EG nanofluids particularly interesting from the point of view of future applications. Adio et al [39] present results of their work on experimental investigation and model development for effective viscosity of magnesium oxide-ethylene glycol nanofluids. They used dimensional analysis, FCM-ANFIS and GA-PNN techniques to prepare model of viscosity depend on temperature and volume fraction of nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…By using the methods of dimensional analysis, the experimental data have been accurately predicted. Based on the methodology employed by Adio et al [29], the nondimensional parameters for the PKF-based nanofluids are presented in equation (7). The function f in equation 7is obtained using nonlinear regression and presented in equation 8:…”
Section: Coefficientmentioning
confidence: 99%